Vitamin D and ω-3 Polyunsaturated Fatty Acids towards a Personalized Nutrition of Youth Diabetes: A Narrative Lecture - Cadario, Francesco (Nutrients, 2022)
After the discovery of insulin, nutrition has become central in the management of diabetes in order to limit glycemic rise after meals, optimize metabolic control, and prevent complications. Over the past one hundred years, international scientific societies have consecutively refined nutritional needs and optimized food intake for the treatment of diabetes. In particular, over the past century, nutrition applied with pumps for the administration of insulin and continuous glucose monitoring have allowed substantial advancement in the treatment of type 1 diabetes mellitus. The role of some substances, such as vitamin D and n-3 polyunsaturated fatty acids, have been proposed without univocal conclusions, individually or in combination, or in the diet, to improve the nutrition of type 1 and type 2 diabetes. This second condition, which is highly associated with overweight, should be prevented from childhood onwards. Personalized nutrition could bypass the problem, reaching a scientific conclusion on the individual subject. This article focuses on childhood and adolescent diabetes, aims to provide a narrative summary of nutrition over the past century, and promotes the concept of personalized nutrition to pediatricians and pediatric diabetologists as a possible tool for the treatment of type 1 diabetes and the prevention of type 2 diabetes.